Religious landscapes in contemporary Spain : the impact of secularization on religious pluralism - Cueva Merino, Julio de la, 1964-; Planet Contreras, Ana I.; Planet Contreras, Ana I.; H. de Larramendi, Miguel (Hernando de Larramendi); H. de Larramendi, Miguel (Hernando de Larramendi) (Sussex studies in Spanish history., 2022)
"Spain is no longer exclusively identified with Catholicism. This book sets out to understand the social dynamics of twenty-first century Spain through the perspective of religion and religious pluralism"--